2020
DOI: 10.1590/1678-4162-11517
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic values of physical and hematological parameters of dogs naturally infected with parvovirus PVC-2: retrospective study of 103 cases

Abstract: Canine parvovirosis is a high mortality disease with acute clinical picture. However, there are few available resources to help stablish prognosis accurately. This study aimed to determine the prognostic threshold values for vital and hematological parameters of dogs naturally infected by the Carnivore protoparvovirus 1 (CPV). A retrospective study of 103 canine parvovirosis cases was carried out. Twenty seven percent of these (28/103) died, 96% (27/28) of which within the first four days of hospitalization. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
2
0
2
Order By: Relevance
“…The severe picture of leukopenia that CA1 presented is indicative of a reserved to poor prognosis, as well as a high number of episodes of emesis and diarrhea represent a group at higher risk of death, which was also observed by Alves et al (2020).…”
Section: /9mentioning
confidence: 88%
“…The severe picture of leukopenia that CA1 presented is indicative of a reserved to poor prognosis, as well as a high number of episodes of emesis and diarrhea represent a group at higher risk of death, which was also observed by Alves et al (2020).…”
Section: /9mentioning
confidence: 88%
“…Terzungwe (23) in Ukraine reported anemia (20.7%), leucopenia (31%), and lymphopenia (27.6%) in a study involving 29 dogs of various breeds and ages with CPV infection. Alves et al (35) in Brazil studied 103 dogs under 1 year old with CPV infection and noted severe leucopenia in 75% of affected dogs, with 40.4% of the leucopenic patients succumbing to the infection. Arslan et al (36) also reported that dogs with CPV infection exhibited a hematocrit (HCT) of 36.97%, lower than the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Oliveira (2020), entretanto, pontua que a antibioticoterapia deve ser administrada apenas quando constam resultados positivos na urocultura, não sendo feita a administração dos medicamentos sem a realização desta, tendo em vista a possibilidade de resistência bacteriana por uso indiscriminado de antibióticos (Moraes et al, 2018;Oliveira, 2020). Luther & Nye (2018), Alves et al (2020), Lacerda et al (2017) e Moraes et al (2018) citam o uso de anti-inflamatórios como Meloxicam na dose de 0,05-0,1 mg/kg, SC, SID e analgésicos como Dipirona na dose de 25 mg/kg, SC/EV, TID e Cloridrato de Tramadol na dose de 2-4 mg/kg, SC, BID, durante e após o processo de desobstrução uretral. De acordo com Lulich et al (2016), gatos obstruídos que passam por técnicas de desobstrução clínica podem apresentar recidivas caso não sejam adicionadas estratégias terapêuticas e métodos alternativos de manejo para minimizar os fatores de riscos patológicos.…”
Section: Desenvolvimentounclassified
“…Finalmente, a conscientização e instrução do tutor acerca dos sinais clínicos do animal com DTUIF obstrutiva é crucial para a prevenção de recidivas e, se necessário, para o tratamento imediato do mesmo (Moraes et al, 2018;Alves, 2020;Oliveira, 2020). Cooper (2014) conclui que, mesmo sendo realizadas as medidas preventivas adequadas, ainda existem possibilidades de recidivas em 40% dos casos, podendo ser necessária a intervenção cirúrgica.…”
Section: Desenvolvimentounclassified